The Influence of Complexity Knowledge and System Thinking on Knowledge Hiding Mediation Psychological Ownership in Private Banking - Surbakti, Geby Gracela Surnina; Emilisa, Netania; Cika, C.; Said, Muhammad Nadhif (Golden Ratio of Human Resource Management, 2026)
The aim of this study is to analyze the effects of complexity knowledge and systems thinking on knowledge hiding, with psychological ownership serving as a mediating variable in private banking services in Central Jakarta. Knowledge hiding represents a critical issue in the banking industry, as highly competitive and stressful work environments may encourage employees to intentionally conceal knowledge, thereby inhibiting cooperation and organizational performance. This study employs a quantitative research design with a hypothesis-testing approach. Data were collected through online questionnaires distributed to 160 respondents selected using purposive sampling. The research instrument was developed and validated through reliability and validity testing. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS software, while mediation effects were examined using the Sobel test. Model adequacy was confirmed through goodness-of-fit testing. The findings indicate that complexity knowledge and systems thinking significantly influence knowledge hiding, both directly and indirectly through psychological ownership. These results enhance understanding of how cognitive and psychological factors shape knowledge-related behaviors in private banking organizations. To mitigate knowledge hiding, management is encouraged to strengthen a culture of knowledge sharing by developing systems thinking capabilities, managing job complexity more transparently, and fostering a collective sense of psychological ownership among employees. Future research is recommended to expand the research context and incorporate additional organizational variables to develop a more comprehensive model.